The difference a Gender Makes - Cook, Marcy (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This article demonstrates the different ways men and women are treated online and the consequences of coming under social media attack. Through numerous examples and personal experience from the unique perspective of a transgender woman who has experienced the Internet as a man and a woman.